BIRTH CERTIFICATE AS AN EFFORT TO MEET CHILDREN'S RIGHTS BY THE DKI JAKARTA SOCIAL SERVICE ON ROAD CHILDREN - Nike Vonika (Politeknik Kesejahteraan Sosial Bandung, 2019)
Birth registration is a form of identity recognition and guarantee and protection of children's rights. Fulfilling this right is the responsibility of the government and the family. However, the existence of street children, where the general phenomenon is that they are separated from their parents, becomes a problem in itself when these street children must be registered to get a birth certificate. This research describes the efforts to fulfill children's rights by the DKI Jakarta government regarding birth certificates for street children. The research method used is a qualitative approach with descriptive research type. The results of this study indicate that the government has issued various policies and efforts so that all Indonesian children get their rights to birth certificates. For street children, child registration can be done through a parent/guardian, where the parent/guardian can be from an orphanage, shelter where the child takes shelter. The policy on the ease of obtaining birth certificates was also implemented, such as free financing, bringing the certificate management agency closer to the sub-district level, and establishing an implementing unit to reach unregistered children so that their birth certificates could be made.